(untitled) (Revista Rupturas, 2022)
Costa Rica is a country full of great privileges due to the geographical position in which it is located, one of these privileges is the great production of water resources that occurs in almost the entire extension of the territory during all times of the year This has led to the promotion of human settlements almost anywhere in the country. These settlements are often supplied with water both for consumption and for the development of productive activities by Associations Administrators of Communal Aqueduct and Sewer Systems commonly known as ASADAS, which has generated that in very different ways all kinds of activities and actions are carried out. To comply with the service to users, as part of a specific experience as a university extensionist teacher, it is intended to capture the work that the University of Costa Rica public institution of higher education had the experience of working with communities where ASADAS operated from a University Community Work project and the impact that this generated on the students who participated.